Relating the Capabilities of the Handicapped to the Human Attribute Requirements of Jobs User's Guide - Johnson, Marion T.; Ohio State Univ., Columbus. National Center for Research in Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The guide is intended to provide educators and potential employers of the handicapped with information on career preparation for the handicapped. The self instructional format is explained to focus on the process of developing work relevant human attributes required for job performance and then relating these requirements to the capabilities of handicapped persons. The guide includes sample instrumentation, illustrations, examples, and analysis from three occupations (general secretary, automotive mechanic, and business data programmer). Guidelines are offered for preparing occupational statements, identifying attribute requirements, selecting survey instrument respondents, developing occupation by attribute and job activity by attribute survey instruments, and developing attribute by exceptionality survey instruments. (CL)
Sponsoring Agency: Bureau of Education for the Handicapped (DHEW/OE), Washington, DC.
Contract Number: G007603970.
ERIC Note: For related documents, see EC 131 335-336.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disabilities; Employment; Job Skills; Prevocational Education; Secondary Education; Student Characteristics; Student Evaluation; Vocational Adjustment; Guides, Non-Classroom.